Portfolio Performance Analysis Using the Treynor Model in the Early Period of the Covid-19 Pandemic - Suharti, Titing; Yudhawati, Diah; Kusumah, Anuraga; Fatimah, Berliani (INOVATOR, 2024)
This study aims to determine portfolio performance using the Treynor model for companies listed on IDX30 in the early period of the COVID-19 pandemic (February-July 2020). This research method is a quantitative descriptive method which in this study tries to analyze, describe and explain the performance of a stock portfolio using the Treynor method in companies listed on IDX30-BEI. The sampling method was purposive sampling method in order to obtain 5 issuers, namely PT. Aneka Tambang Tbk, PT Bank Negara Indonesia Tbk, PT. Erajaya Swasembada Tbk, PT. Indofood Sukses Makmur Tbk and PT. Kalbe Farma Tbk. The results showed that the beta portfolio or the highest investment risk was found in the portfolio composition 22. The lowest risk was in the portfolio composition 12. The highest rate of return in portfolio composition is 28. The lowest rate of return is portfolio 16. Optimal portfolio performance using the Treynor method is found in the 18th portfolio.